Students’ Perceptions Regarding the Change in the Conversion of NIK to Npwp in Increasing Tax Compliance (Case Study of Students at Pertiwi University) - Aurora, Vini Widya; Mulyani, Sri; Audina, Bella Puspita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to understand students' perceptions regarding the conversion of the National Identification Number (NIK) into the Taxpayer Identification Number (NPWP) in improving tax compliance. The case study was conducted on students at Pertiwi University. This research is a descriptive study utilizing a quantitative approach. The research findings reveal that 36.5% of students agreed with the socialization efforts regarding the conversion of NIK to NPWP, 42.2% agreed that the conversion process would simplify tax administration for taxpayers, 45.3% agreed that the regulation for conversion was intended to reduce the number of unregistered taxpayers, 42.2% agreed with the government’s establishment of the NIK to NPWP conversion, and 50% agreed with the government's implementation of this conversion. The results suggest that students have a positive perception of the NIK to NPWP conversion. They recognize the benefits and importance of having an NPWP, which encourages increased tax compliance among students. This study offers insights for both the government and educational institutions to enhance socialization and education on tax administration, particularly regarding the NIK to NPWP conversion, to boost awareness and tax compliance within the community.